MIP-Modified Porous Silicon Optical Sensor for Interleukin-6 Label-Free Quantification - Valeria Nocerino; Giulia Siciliano; Monica Bianco; Ilaria Rea; Principia Dardano; Maria Serena Chiriacò; Francesco Ferrara; Giuseppe Gigli; Elisabetta Primiceri; Luca De Stefano (Biosensors)
In this study, we present an innovative optical biosensor designed to detect Interleukin-6 (IL-6), a pivotal cytokine implicated in many pathological conditions. Our sensing platform is made of a porous silicon (PSi) nanostructured substrate modified with a thin (~5 nm) molecularly imprinted polymer (MIP), ensuring both high specificity and sensitivity toward IL-6 molecules. The fabrication process involves electrochemical etching of silicon chips to create the porous structure, followed by the electrodeposition of the MIP, which is tailored to selectively bind the IL-6 target. Extensive testing over a broad IL-6 concentration range demonstrates a clear, proportional optical response, yielding a limit of detection (LOD) of 13 nM. Moreover, the biosensor robustness was verified by evaluating its performance in bovine serum, a complex biological matrix. Despite the presence of various interfering components, the sensor maintained its selectivity and displayed minimal matrix effects, underlining its practical applicability in real-world diagnostic scenarios.